Brand Awareness Analysis Of Sukarara Woven Cloth Motifs - Fitria Ika Agustina; Amiruddin Kalbuadi; Sri Septin Adiningsih (Business Management, 2026)
This research aims to determine and analyze the level of awareness (brand awareness) of tourists regarding the Sukarara woven fabric motifs they purchase. The type of research used in this research is descriptive research with a quantitative approach with a sample of 120 respondents who met the criteria by sampling using a non-probability sampling technique. The data source used in this research is primary data with Documentation, Observation and Questionnaire data collection methods. The research results show that the level of Brand Awareness towards Sukarara woven fabric motifs is at the Brand Recall level. This can be seen from the Brand Awareness calculation results of 2.89 where the Brand Recall level is on a scale of 2.52 – 3.27, which means that the level of knowledge of tourists regarding the sukarara woven fabric motif in Brand Awareness is at the Brand Recall level